Public Policy and the Shaping of Disability: Incidence Growth in Educational Autism - Baker, Dana Lee (Education Policy Analysis Archives, 2004)
Autism has gained the attention of policy makers and public administrators in recent years. The surge in prevalence, in tandem with a growing social preference for community inclusion of individuals with disabilities, strains a variety of policy infrastructures. Autism and related disorders, which were first described in 1943, were originally thought to be extremely low incidence and usually coincident with mental retardation. In accordance with the disability policy paradigm of the era, public services for autism were provided predominantly in institutional settings. Since then, however, autism and related disorders have come to be understood as more common than was originally thought and more rarely associated with mental retardation. In this article, shift-share analysis is used to gain insight into how the growth in autism incidence is being differentially experienced and recorded within a single arena of policy across the United States. The challenges associated with a sudden growth in supply (that is the number of children with autism), while unique to autism in some respects, include aspects that are similar for other disabilities and in policy challenges in other arenas. Especially since the implementation of the Government Performance Results Act of 1996, there is increased pressure to create public policy infrastructures that are anchored by clearly cut categorical service delivery. If the categories themselves leave significant room for interpretation and their use actually has a shaping effect on the target population, then it is important to administration and policy evaluation to understand how the effect is playing out.